Antiangiogenic Effect Of The Chloroform Extract Of Tinospora crispa (L.) Miers Stem In The Chick Embryo Chorioallantoic Membrane (CAM) Induced By bFGF - Asih Triastuti (EKSAKTA: Journal of Sciences and Data Analysis, 2010)
Cancer is one of the most complex disease involving molecular process cause it is hard to be cured. There are many natural compounds which have been used empirically in the society in order to treat cancer. One of them is a kind of herbal medicine called ‘Brotowali’ (Tinospora crispa (L.) Miers). The objective of this research was  to know antiangiogenic effect of the chloroform extract of  brotowali stem using CAM method induced by bFGF. In this research, the inhibition test is done by the CAM at 9 day chick embryo divided  into  seven groups of treatment. Group I is  as the paper disc controller, group II as the bFGF controller, group III as  bFGF +  DMSO 0,8% solvent controller, group IV, V, VI and VII, as the group that conduct the angiogenesis inhibition test. The last four group were given 10 ng of bFGF each and the chloroform extract of brotowali stem with the doses of 15 μg/ml, 60 μg/ml, 240 μg/ml and 960 μg/ml. After having been incubated for 3 days (egg at 12 day), CAM were carefully observed  macroscopically and microscopically. The result showed that  the chloroform extract of brotowali stem can  inhibit the angiogenesis in CAM induced by bFGF. It show that the angiogenesis inhibition for the dose of the chloroform extract of  brotowali stem were successively rise  due to the dose increment, with angiogenic potency  31,87±9,01%,  43,12±8,01%, 53,44±2,70% and  62,81±4,74%.   Keywords : cancer, angiogenesis, Tinospora  crispa (L.) Miers, bFGF, CAM